(untitled) (Journal of the Professional Association for Cactus Development, 2006)
The health-promoting properties of edible fruits from Opuntia ficus-indica have been the object of recent interest. Scientific evidence has been provided about benefits from the consumption of the fruits in humans, with special attention to the non-nutritive components as potentially active antioxidant phytochemicals. Information about bioavailability and bioactivity of betalains, mode of action as antioxidants in cells, and other biological models are now available. The use of cactus pear components as nutraceuticals and functional food is discussed.